Leadership without "the led": a case study of the South Wales Valleys. Issue 3 (15th January 2021) - Harding, Nancy
Abstract : Purpose: This paper aims to disrupt assumptions about leadership by arguing those who are ostensibly "followers" may be utterly insouciant towards the existence of people categorised as "leaders". It contributes to anti-leadership theories. Design/methodology/approach: This article uses an immersive, highly reflexive methodology to explore subjective meanings of leadership at community levels ostensibly governed by local government leaders. It uses a case study of the South Wales Valleys, one of the hubs of the Industrial Revolution in the 19th century but now economically deprived. Findings: Through drawing on their rich and complex history, the author shows how in these communities there is a culture of neo-communitarianism that is anti-leadership and suspicious of attempts to establish hierarchies of superior over inferior. The author explores the complex webs of meaning through which ancient experiences reverberate like dead metaphors, informing contemporary understandings without conscious awareness of such a heritage. This is a history in which "leaders" betrayed or oppressed and exploited the population, which in response turned against hierarchies and evolved practices of self-government that continue today, invisible and unrepresentable within the wider culture. Research limitations/implications: The study draws on contemporary feminist research methods that emphasise subjectivity, flux and change. These are often not understood by readers not accustomed to stepping out of a positivist onto-epistemological frame. Practical implications: The paper challenges the universalising tendencies of leadership theories that assume a shapeless mass; "followers" await the advent of a leader before they can become agentive. Social implications: The paper offers insights into a day-to-day world that is rarely explored. Originality/value: The article demonstrates how emerging forms of qualitative research give insights into communities that undermine dominant, universalising theories of leadership, followership and government more generally.